Kajian Visual Relief Jalan Salib di Bukit Doa Getsemane Kabupaten Samosir - Rencus Aslober Sinaga; Sumarsono Sumarsono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the relief visualization of the way of the cross based on the application of the proportional principle of the human body and also based on the application of perspective and realist imagery that appears in the relief. The method used in this research is descriptive qualitative, namely by using theoretical studies as a data base, then collecting data through direct observation to the research site, interviewing sources and other sources related to the research. Then conduct a documentation study, then analyzed based on theoretical studies and literature study. The population in this study consists of 14 reliefs that tell about the way of the cross and are analyzed based on theoretical foundations. The results of this study are: The proportion of humans in the relief of the way of the cross is not in accordance with the theory or principle of the golden section which states that the ideal proportion of the human body is in the range of 7.5 to 8 times the head as a comparison; The perspective principle on the relief of the way of the cross has not been fully implemented properly; The relief of the cross path at the location of the Getsemane Prayer Hill Faith Tour is a work of art that shows a realist image well where the depiction of the object is in accordance with the fact or the original and all objects in the relief appear to blend with one object with another.